PEMODELAN INFRASTRUKTUR HIDROGEN UNTUK APLIKASI FUEL CELL DAN DAMPAKNYA TERHADAP ERA EKONOMI HIDROGEN STUDI KASUS DI KOTA SEMARANG - Bayu Murti; Sunu Arsy Pratomo (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
The hydrogen economy is a shift in the use of fossil energy to energy derived from hydrogen. Currently, Energy experts are trying to find fuel from new and renewable energy, especially in the transportation sector. This study seeks to determine the profile of energy consumption in the city of Semarang, especially in the transportation sector with simulation calculations in a certain year. By knowing the profile of energy consumption in the transportation sector in the city of Semarang, the output of this research is a planning study to build hydrogen economic infrastructure and make possible steps. At the end of this paper, it will be known how big the potential for hydrogen infrastructure development is so that later it can be a guide in determining the right policy in carrying out hydrogen infrastructure development in the city of Semarang. The design capacity of hydrogen production at PT. SAMATOR is 1000 m3/hour. Production breakdown per day : 550 m3/hour x 24hours = 13,200m3. If the production is maximized for 360 days per year, the total hydrogen production in Semarang is 4,752,000m3. In 2020, the demand for hydrogen in the city of Semarang = 1,955,780 m3. With this research data, it can be analyzed that hydrogen production in the city of Semarang can meet the needs of hydrogen for transportation in the city of Semarang.